Hvad skal vi bruge videnskabsteori til? Om videnskabsteori på professionsuddannelser - Krause-Jensen, Niels Henrik; Hansen, Brian Benjamin (Tidsskrift for Professionsstudier, 2024)
This article addresses the question of what role philosophy of science programs can and should play in professional education and for professions and practice development more generally. The article is based on a series of workshops with educators in philosophy of science from a broad range of programs at VIA University College. We argue that it requires a new understanding of philosophy of science if it is to be relevant to professions and practices. Traditionally, philosophy of science has either been understood as the question of what science is and should be, or it has been understood more narrowly as a collection of methodological doctrines. We propose understanding the philosophy of science as a curious and investigative type of questioning that concerns the professional and practical knowledge base, including research and science. The focal point of this questioning can be described as a shift in focus, a shift from focusing on a particular matter to focusing on how one thinks about the matter. We demonstrate how this shift of focus is more dynamic way to work with philosophy of science in a professional and practical context.